Composite-Dentin Bond Strength of Two Adhesives in Different Conditions - P. Samimi; A. Filsoufi; K. Fathpour (Wolters Kluwer Medknow Publications, 2007)
Introduction: The purpose of this study was to evaluate the effect of thermo-cycling and curing mode of composites (light and chemical curing) on dentin bond strength of one all-in-one and an one-bottle bonding systems.Methods and Materials: Occlusal enamels of eighty caries-free third molars were ground with a model trimmer to create flat surfaces in superficial dentin for bonding, and randomly divided into 4 groups. Teflon molds with 1 mm internal diameter were mounted on the flat surfaces, Prompt L-pop (all-in-one system) (3M-ESPE) and Single-Bond(one-bottle system) (3M-ESPE) were used and restored with FiltekZ250 (light-cured composite) (3M-RSPE) and Concise (chemically cured composite) (3M-ESPE) composites. Specimens were stored in 37°c distilled water for 24 hours. 10 specimens of each group were thermo-cycled 500 times between 5°c to 55°c. Micro- shear bond strength test was done with 0.5mm/min crosshead speed (Dartec, England). The data were analyzed by ANOVA and Duncan's tests.Results: The mean shear bond strengths of two adhesive systems with light-cured composite showed no significant differences with and without thermo-cycling (P<0.05). Also, there was no significant difference between bond strength of two adhesive systems with light cured composite (P<0.05). Use of chemically cured composite reduced the bond strength of Single-Bond significantly (P<0.001). There was not any bond between chemically cured composite to dentin, using prompt L-pop.Discussion: Thermal cycles, in the range that we used them, did not have any influence on the bond strengths of two mentioned systems. The effect of increasing cycles should be evaluated. Use of chemically cured composite decreases the bond strength of Single Bond and there was no bond between this kind of composite and Prompt L-pop system. So these systems, especially Prompt L-pop, shouldn't be used with chemically cured composite in routine dental treatments.